Exploring the association between phytopharmaceutical use and antibiotic prescriptions in upper respiratory infections: results from a German cohort study evaluating the impact of naturopathy qualifications of general practitioners using routine data - Wetzel, Anna-Jasmin; Laux, Gunter; Joos, Stefanie; Musselmann, Berthold; Valentini, Jan (Frontiers in Medicine, 2024)
Background: Antibiotic resistance is a significant global health threat, exacerbated by inappropriate prescribing practices, particularly for upper respiratory infections that are predominantly viral. Complementary and Integrative Medicine (CIM), including the use of phytopharmaceuticals, offers a potential strategy to reduce antibiotic prescriptions.Objective: This study aimed to describe the impact of General Practitioners' (GPs) naturopathy (NP) qualifications and phytopharmaceutical prescriptions on the rate of antibiotic prescribing for upper respiratory infections (RTI).Methods: We conducted a retrospective cohort study using routine data from the CONTinuous morbidity registration Epidemiologic NeTwork (CONTENT), which includes over 200,000 patients across four federal states in Germany. The study included data from n=36 GPs who recorded at least one ICD-10 diagnosis of RTI. Antibiotic and phytopharmaceutical prescriptions were identified and analyzed through mixed-effects logistic regression models to explore the influence of GPs' naturopathy qualifications and phytopharmaceutical use on antibiotic prescribing patterns.Results: The study included 40,344 patients managed by 36 GPs. Prescriptions of phytopharmaceuticals significantly reduced the likelihood of antibiotic use (OR 0.48, 95% CI 0.45-0.52). Additionally, holding a naturopathy qualification was associated with lower rates of antibiotic prescriptions (OR 0.73, 95% CI 0.69-0.78). The interaction between naturopathy qualification and phytopharmaceutical prescriptions also showed a significant effect (OR 1.43, 95% CI 1.27-1.62). Patient's year of birth influenced prescribing patterns indicating a reduction of antibiotic prescriptions for younger patients, while patients' gender did not reveal a significant effect.Conclusions: Prescriptions of phytopharmaceuticals were significantly associated with a decrease antibiotic prescriptions among GPs, especially when combined with naturopathy qualifications. Training in naturopathic approaches could enhance antibiotic stewardship efforts in primary care settings, suggesting that broader integration of CIM elements into medical training could be beneficial in mitigating antibiotic resistance.